Peran Masjid Sekitar Pasar Raya Dalam Mengurangi Praktik Prostitusi Di Pasar Raya Padang - Ibrahim Mufiq; Ahmad Rivauzi (Universitas Pahlawan Tuanku Tambusai, 2024)
Pasar Raya Padang is known as an area bustling with activity, hosting various institutions such as mosques serving as places of worship, the Civil Service Police Unit (Satpol PP) enforcing local regulations, specifically Padang City Regulation Number 11 of 2005 concerning Public Order and Community Tranquility in relation to Article 10 Paragraph (2) on prostitution, and the local police (Polresta) who act as the frontline defense against prostitution practices. However, the phenomenon of prostitution can still be found in the area, highlighting the complexities in monitoring and social control over behaviors that contradict social and religious norms. This study aims to describe the role of mosques in Pasar Raya Padang in providing knowledge about the dangers of prostitution through various aspects, including legal aspects, dangers, and social impacts. This research employs qualitative methods, utilizing in-depth interviews and observations in several mosques in the area. The findings reveal that mosques around Pasar Raya Padang play a crucial role in educating the public about the dangers of prostitution through various aspects, including legal perspectives, dangers, and social impacts.